2017
DOI: 10.1002/jsfa.8462
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of partial least squares and random forests for evaluating relationship between phenolics and bioactivities of Neptunia oleracea

Abstract: BACKGROUND: Neptunia oleracea is a plant consumed as a vegetable and which has been used as a folk remedy for several diseases. Herein, two regression models (partial least squares, PLS; and random forest, RF) in a metabolomics approach were compared and applied to the evaluation of the relationship between phenolics and bioactivities of N. oleracea. In addition, the effects of different extraction conditions on the phenolic constituents were assessed by pattern recognition analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The method of Lee et al [ 42 ] with slight modifications was adopted for sample preparation. For measurement of 1 H NMR spectra of the solvent extracts, approximately 5 mg of extract was dissolved in 600 µL deuterated acetone in a 2 mL Eppendorf tube.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of Lee et al [ 42 ] with slight modifications was adopted for sample preparation. For measurement of 1 H NMR spectra of the solvent extracts, approximately 5 mg of extract was dissolved in 600 µL deuterated acetone in a 2 mL Eppendorf tube.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of radical scavenging properties of C. calcitrans extracts were performed by following method as described by Lee et al [ 42 ]. 100 µL methanolic DPPH solution was prepared was mixed with 50 µL of sample extracts.…”
Section: Methodsmentioning
confidence: 99%
“…The adsorption process was conducted over 24 h at 25 • C. The experiment was carried out on OPL extract solutions of different pH (5, 7, and 9; adjusted with 1 M HCl or 1 M NaOH), in triplicate. At 0, 5,10,15,20,25,30,40,50,60,120,180,240,300,360,480, and 1440 min time points, 0.125-mL aliquots of the treated OPL extract were withdrawn for TFC determination. The adsorption kinetics equation for each resin was accordingly established for each.…”
Section: Adsorption Kinetics Of Opl Total Flavonoids On the Selected mentioning
confidence: 99%
“…The 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assay was performed as described earlier by Lee et al [40], with some modifications. Test concentrations of the OPL extract ranging from 0.7 to 100 µg·mL −1 were prepared by serial dilutions of a 0.1 mg/mL stock solution.…”
Section: Determination Of Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
“…Besides, to identify antioxidants and α-glucosidase inhibitors from natural resources, N. oleracea has been studied by our research group for its free radical scavenging and α-glucosidase inhibitory properties. The results have shown that this plant is a prominent source of free radical scavengers and α-glucosidase inhibitors; with phenolics as the potential candidates for these active compounds [11, 12].…”
Section: Introductionmentioning
confidence: 99%